'You're not sure that you are gay yet': The perpetuation of the 'phase' in the lives of young disabled LGBT + people. (June 2020) - Toft, Alex; Franklin, Anita; Langley, Emma
Contemporary discourse on sexuality presents a picture of fluidity and malleability, with research continuing to frame sexuality as negotiable, within certain parameters and social structures. Such investigation is fraught with difficulties, due in part to the fact that as one explores how identity shifts, language terms such as 'phase' emerge conjuring images of a definitive path towards an end-goal, as young people battle through a period of confusion and emerge at their true or authentic identity. Seeing sexuality and gender identity as a phase can delegitimise and prevent access to support, which is not offered due to the misconception that it is not relevant and that one can grow out of being LGBT+. This article explores the lives of disabled LGBT + young people from their perspective, using their experiences and stories to explore their identities and examine how this links to the misconception of their sexuality and gender as a phase. Taking inspiration from the work of scholars exploring sexual and gender identity, and sexual storytelling; the article is framed by intersectionality which allows for a detailed analysis of how identities interact and inform, when used as an analytic tool. The article calls for a more nuanced understanding of sexuality and gender in the lives of disabled LGBT + young people, which will help to reduce inequality and exclusion.